3(3p+4)-4(p+8)=

Simple and best practice solution for 3(3p+4)-4(p+8)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(3p+4)-4(p+8)= equation:


Simplifying
3(3p + 4) + -4(p + 8) = 0

Reorder the terms:
3(4 + 3p) + -4(p + 8) = 0
(4 * 3 + 3p * 3) + -4(p + 8) = 0
(12 + 9p) + -4(p + 8) = 0

Reorder the terms:
12 + 9p + -4(8 + p) = 0
12 + 9p + (8 * -4 + p * -4) = 0
12 + 9p + (-32 + -4p) = 0

Reorder the terms:
12 + -32 + 9p + -4p = 0

Combine like terms: 12 + -32 = -20
-20 + 9p + -4p = 0

Combine like terms: 9p + -4p = 5p
-20 + 5p = 0

Solving
-20 + 5p = 0

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '20' to each side of the equation.
-20 + 20 + 5p = 0 + 20

Combine like terms: -20 + 20 = 0
0 + 5p = 0 + 20
5p = 0 + 20

Combine like terms: 0 + 20 = 20
5p = 20

Divide each side by '5'.
p = 4

Simplifying
p = 4

See similar equations:

| 16x+24=16x+24 | | .25(3x-16)+.25x=5.333 | | -2.3-3y-2.5-y=-3y-3.6 | | 4(x+3)=2x+74 | | Log(x+3)=2.1 | | 78+2x=100 | | 6(3b-8)=2(6b-3) | | 15+3m=27 | | -6.3-3z-1.5-z=-3z-5.9 | | 4b+b^2=0 | | -1x^1+1= | | .20x+.35(30)=29.5 | | 4(x-10)=-6(x-2)-6 | | (-2a/b^4)^2 | | .20+.35(30)=29.5 | | y=x^2+2ax+4 | | .355=(×^×)/((2.82-2×)(2.83-2×)(2.83-×) | | -46+34= | | (3/10)-3 | | 62=6x-10 | | f(3)=0/21= | | 27x^2+3x-10= | | 7x-(3x+2)=62 | | 8/5m=4/15 | | 45/?=13 | | 8x+4=13+6x | | In(x+5)+(x-5)=(4x+7) | | 8/9-1/8 | | f(7)=4/49= | | v-5=12 | | 2x-10=6x^1 | | 12x^2-43x+35= |

Equations solver categories